Pojęcie „zdolność” w narracji studentów angielskich i polskich. Ujęcie kognitywne - Gierczyk, Marcin (Studia Edukacyjne, 2017)
The purpose of this publication is to show how students from Poland and England defineand understand the concept of ‘giftedness’. The analyses result from the author’s research conducted over the years 2013-2016. In the interviews, the students presented their own associations with the matter. Materials collected from 30 respondents, including 15 students from Śląski University and from a Lublin University and 15 students from Oxford University, showed that the concept of ‘giftedness’ is understood by Polish students identically to English students. ‘Giftedness’ was definedby a series of connotations: ‘creativity’, ‘talent’, ‘ability to do something’, ‘predisposition’, and ‘organization of thinking’.